Prognostication of Cardiovascular Outcomes in Patients with Acute Coronary Syndromes - Babarskiene, M. R.; Vencloviene, J.; Luksiene, D.; Milvidaite, I. (Elektronika ir Elektrotechnika, 2011)
Ischemic heart disease is the leading cause of death in Europe among males over 45 years of age and females older than 65. The aim of the study: to evaluate the informative value of the models in ACS patients using GRACE (GR) risk score, to identify additional informative indicators for short-term and long-term prognosis following ACS, and to evaluate the prognostic reliability of the integrated model. The study included 1491 patients who in 2005 were treated for ACS in the Department of Cardiology, the Hospital of Kaunas University of Medicine. We devised an adjusted prognostic index for making short and long-term prognosis in patients with acute coronary syndromes (STEMI and NSETMI). Following adjustment of the GR scores, the prognostic value improved for STEMI patients. Ill. 2, bibl. 12, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.292